COMPARATIVE HISTOLOGIC STUDY IN ENDOMETRIUM OF PREGNANT AND COWS WITH SYMPTOM FREE STERILITY - ΣΕΪΤΑΡΙΔΗΣ, Κ.; ΡΑΝΤΣΙΟΣ, Α.; ΕΛΕΖΟΓΛΟΥ, Β. (Journal of the Hellenic Veterinary Medical Society, 1974)
Histologic examinate of the endometrium of 37 cows with symptom free sterility (21 during folicular and 16 during luteal phase) and the endometrium of 26 pregnant cows (1st - 4th month of pregnancy) demonstrated that 94.6 % of the former and 80,8 % of the latter show various degrees of inflammatory changes. These changes were mainly plasma cell and lymphocyte cell infiltrations particularly during the folicular phase (P<0,001 versus pregnant cows endometrium), inflammatory perivascular infiltrations and of the glands of endometrium, particularly during the luteal phase (P<0,01 versus pregnant cows) and connective tissue development during pregnancy (P<0,01).